Egypt, Canaan and Israe l history, imperialism, ideology and literature : proceedings of a conference at the University of Haifa, 3-7 May 2009 - Bar, Shay.; Kahn, Dan'el.; Shirley, J. J. (Culture and History of the Ancient Near East, 2011)
The proceedings of the conference "Egypt, Canaan and Israel: History, Imperialism, Ideology and Literature" include the latest discussions about the political, military, cultural, economic, ideological, literary and administrative relations between Egypt, Canaan and Israel during the Second and First Millennia BC incorporating texts, art, and archaeology. A diverse range of scholars discuss subjects as wide-ranging as the Egyptian-Canaanite relations in the Second Intermediate Period, the ideology of boundary stelae, military strategy, diplomacy and officials of the New Kingdom and Late Period, the excavations of Beth-Shean and investigations into the Aruna Pass, and parallels between Biblical, Egyptian and Ancient Near Eastern texts. Such breadth in one volume offers a significant contribution to our understanding of the interactions between the civilizations of the ancient Near East.